2005
DOI: 10.1038/sj.leu.2403915
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological relevance of single-nucleotide polymorphisms and acquired somatic mutations of the BCL6 first intron in follicular lymphoma

Abstract: Genetic modifications of the BCL6 gene in lymphoma include translocations, deletions, and somatic mutations (SM) of the 5 0 noncoding region. Three single-nucleotide polymorphisms (SNPs) of the major mutation cluster region (MMC) have been reported, including two substitutions (397G/C, 502G/A) and one deletion (520DT). Clinical and biological relevance of these SNPs are unknown. Based on a case-control study, BCL6 SNPs frequencies were assessed in 97 t(14;18) follicular lymphomas (FL) and in 54 lymphomas with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
(42 reference statements)
3
7
1
Order By: Relevance
“…In this study we have found upregulation of BCL6 gene expression that was in concordance with others who found that the levels of BCL6 gene expression and protein have been demonstrated to expect the clinical outcome of DLBCL (Lossos et al, 2001). The BCL6 findings from the pooled data set were consistent with our study (Zhang et al, 2005) but do not provide support for two other previous studies of follicular lymphoma (Jardin et al, 2005). Other study examined tumors with a variety of different BCL6 translocations and found no increase in total BCL6 mRNA levels in the NHL specimens harboring BCL6 gene translocation (Lossos et al, 2003).…”
Section: Discussionsupporting
confidence: 78%
“…In this study we have found upregulation of BCL6 gene expression that was in concordance with others who found that the levels of BCL6 gene expression and protein have been demonstrated to expect the clinical outcome of DLBCL (Lossos et al, 2001). The BCL6 findings from the pooled data set were consistent with our study (Zhang et al, 2005) but do not provide support for two other previous studies of follicular lymphoma (Jardin et al, 2005). Other study examined tumors with a variety of different BCL6 translocations and found no increase in total BCL6 mRNA levels in the NHL specimens harboring BCL6 gene translocation (Lossos et al, 2003).…”
Section: Discussionsupporting
confidence: 78%
“…A preferential distribution of mutations in several regions has been reported. 37,38 We also observed clustering of mutations in three regions, but only one region (80-123) has been reported previously in DLBCLs. 29 Although one report 37 suggested that mutations in one cluster (420-443) were associated with increased protein expression, we did not find any correlation of BCL6 mRNA or protein expression with any of the intronic clusters, thus confirming other reports.…”
Section: Discussionmentioning
confidence: 52%
“…The first mutation cluster (80-123) has been reported by others. 37,38 In subgroup analysis, the presence of two major clusters was observed in the GCB subgroup (277-316 and 470-513), but clustering was not discernable in the other subgroups probably because of the lower number of cases with mutations. In agreement with previous studies, three single-nucleotide polymorphisms (SNPs) in the MMC were observed at positions 397 (C-G; 20%), 502 (A-G; 10%) and 520 (del T; 10%).…”
Section: Bcl6 Gene Mutations In Dlbcl Subgroups and Correlation With mentioning
confidence: 99%
See 1 more Smart Citation
“…No significant difference was found concerning allele or genotype frequencies between FL and controls, which is in contrast to the result by Lossos et al 5 The previously reported higher risk of transformation for FL patients with the C allele could not be verified (P ϭ .8). 7 In conclusion, we could not verify earlier findings by Lossos et al 5 or Jardin et al 7 concerning the associations between the BCL6 397G/C polymorphism and FL and transformed DLBCL. However, a highly significant difference in allele frequency (P Ͻ .001) of the BCL6 397G/C polymorphism was evident between GC-DLBCL and non-GC DLBCL, with a preference for the C allele in the GC group and a preference for the G allele in the non-GC group.…”
Section: Responsecontrasting
confidence: 55%